Preparation method of low-expansion silicon-carbon negative electrode material as well as product and application of low-expansion silicon-carbon negative electrode material
By preparing low-expanded silicon carbon anode material, the performance attenuation problem of silicon anode material due to volume expansion in lithium-ion batteries is solved, and the battery performance with high cycle stability and low expansion rate is achieved.
Patent Information
- Application Number
- CN202411814240.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-11
- Publication Date
- 2025-03-25
AI Technical Summary
The silicon negative electrode material in lithium-ion batteries will undergo violent volume expansion during the charging and discharging process, resulting in the shedding of active substances and the inability to continuously form a solid electrolyte interface (SEI) film, which will lead to rapid attenuation of battery performance.
A low-expanded silicon carbon negative electrode material is used to prepare a thermoset phenolic resin by mixing aldehyde monomers, phenolic monomers, cyclohexamethyltetramine and alumina evenly, and heating polymerization is used to obtain a thermoset phenolic resin, and calcining at high temperature to obtain high-strength carbon, followed by physical activation and silicon deposition, and finally carbon coating is carried out to prepare a low-expanded silicon carbon negative electrode material.
The low-expanded silicon-carbon anode material prepared by this method has high cycle stability and low expansion rate, which significantly improves the electrochemical performance of lithium-ion batteries.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of lithium-ion batteries, and specifically relates to a preparation method of a low-expansion silicon-carbon negative electrode material, and a product and application thereof. Background Art
[0002] In lithium-ion batteries, the cathode materials are mainly lithium iron phosphate (LiFePO4) and ternary (Li(Ni x Co y Mn 1-x-y )O), the negative electrode material is mainly graphite. However, with the continuous improvement of the mileage requirements of electric vehicles and the continuous development of the low-altitude economy, the research on battery energy density has become a hot topic at present; the energy density of graphite, a negative electrode material for commercial lithium-ion batteries, is only 200-300Wh / kg, which has certain limitations in meeting the increasing mileage requirements; therefore, finding new negative electrode materials has become a hot topic in lithium-ion battery research. Silicon has many advantages as a negative electrode material, the most notable of which is its ultra-high theoretical specific capacity of 4200mAh / g. This high specific capacity makes silicon have great potential as the next generation of high energy density negative electrode materials. However, silicon negative electrode materials will undergo drastic volume expansion during the charging and discharging process, which limits its use in commercial applications; during the charging and discharging process, silicon will undergo alloying reaction to store lithium ions, accompanied by a volume expansion of about 300%. This drastic volume change causes the active material to fall off and makes it impossible for the solid electrolyte interface (SEI) film to continue to form, resulting in rapid attenuation of battery performance in practical applications.
[0003] In response to the problems of silicon negative electrode materials themselves, three methods are usually used: First, to improve its performance by nano-sizing silicon. Since the diffusion rate of lithium ions in solids is slow, the diffusion distance of lithium ions from the silicon surface to the center can be shortened by nano-sizing silicon materials, thereby improving the charge and discharge rate and cycle stability. The second is to use silicon / carbon composite materials. Carbon materials have good conductivity and cycle stability, and can be used as a coating layer for silicon materials to buffer the volume change of silicon materials and protect their contact with the electrolyte, which is conducive to the formation and stability of SEI film. The third is to improve the performance of silicon negative electrode materials through microstructure design. However, the silicon-carbon materials obtained by these methods are difficult to use in lithium-ion batteries in large proportions. This is because these methods can reduce volume expansion to a certain extent, but this is far from enough; and to truly solve the expansion performance of silicon-carbon materials, it is necessary to start with silicon nano-sizing and porous carbon substrates. Therefore, the size of small silicon particles is very important, and the modification and pore size regulation of porous carbon substrates are particularly critical.
[0004] In view of this, the present invention is proposed. Summary of the invention
[0005] In response to the above problems, the present invention discloses a method for preparing a low-expansion silicon-carbon negative electrode material. The porous carbon prepared by a specific method has high strength, high conductivity and excellent pore structure. The silicon-carbon negative electrode material prepared with it as the base has both high cycle stability and low expansion rate.
[0006] To achieve the above purpose, the specific technical solution of the present invention is as follows:
[0007] In a first aspect, the present invention provides a method for preparing a low expansion silicon-carbon negative electrode material, comprising:
[0008] (S1) uniformly mixing an aldehyde monomer, a phenol monomer, cyclohexamethylenetetramine and alumina, heating and polymerizing to obtain a thermosetting phenolic resin, and then calcining at a high temperature to obtain a high-strength carbon;
[0009] (S2) physically activating the high-strength carbon to obtain high-strength porous carbon;
[0010] (S3) Using the high-strength porous carbon as a substrate, sequentially performing silicon deposition and carbon coating to prepare the low-expansion silicon-carbon negative electrode material.
[0011] The present invention uses aldehyde monomers and phenol monomers as raw materials, and additionally adds cyclohexamethyltetramine and aluminum oxide, and obtains thermosetting phenolic resin by in-situ preparation. It is found through experiments that the addition of cyclohexamethyltetramine can be used as a polymerization catalyst and a curing agent. More importantly, it can optimize the pore structure of the porous carbon prepared subsequently, so that it has a suitable microporosity and pore volume, and forms a three-dimensional network structure, thereby enhancing its formation and stability; the introduction of aluminum oxide can promote the phase change of carbon materials during the subsequent high-temperature calcination process, from amorphous carbon to glassy carbon, further enhancing the hardness of the material and having high conductivity, and improving the integrity and stability of the porous carbon.
[0012] Further comparative tests found that if hexamethyltetramine was not added, the pore-forming effect was poor, the effective micropores were few, and there was a large amount of floating silicon on the porous carbon surface, resulting in poor cycle stability of the assembled battery, low capacity, and high electrode expansion rate.
[0013] Further comparative tests found that if alumina is not added, the phase transition from amorphous carbon to glassy carbon will not occur. High temperature will cause part of the pore structure to collapse, the original pore volume will be reduced, and the specific surface area will be reduced, which is not conducive to the subsequent deposition of nano-silicon particles. In addition, due to the change in the pore structure, the strength of the porous carbon is low, resulting in poor cycle stability of the assembled battery and a high electrode expansion rate.
[0014] Further comparative experiments found that if cyclohexamethylenetetramine is replaced with other common catalysts and / or curing agents prepared in phenolic resin, such as sodium hydroxide, the prepared porous carbon will have more macropores, which not only has poor integrity and stability, but also the nano-silicon particles are easily agglomerated in the macropores, increasing the resistivity and resulting in poor electrochemical performance of the assembled battery.
[0015] In an optional embodiment, step (S1) includes at least one of the following features (1) to (6):
[0016] (1) The aldehyde monomer is selected from formaldehyde;
[0017] Optionally, an aqueous formaldehyde solution is used;
[0018] Further optionally, the concentration of the formaldehyde aqueous solution is 35-40 wt %.
[0019] (2) The phenolic monomer is selected from one or more of phenol, hydroquinone, and phloroglucinol;
[0020] (3) The molar ratio of aldehyde monomer to phenol monomer is 2:(0.01-2);
[0021] Optionally, the molar ratio of the aldehyde monomer to the phenol monomer is 2:(0.1-1).
[0022] (4) The molar ratio of cyclohexamethyltetramine, aluminum oxide and aldehyde monomer is (0.001-0.2): (0.001-0.05): 2;
[0023] Optionally, the molar ratio of cyclohexamethyltetramine, aluminum oxide and aldehyde monomer is (0.005-0.15):(0.005-0.04):2.
[0024] Further optionally, the molar ratio of cyclohexamethyltetramine, aluminum oxide and aldehyde monomer is (0.01-0.1):(0.01-0.04):2.
[0025] It was found through experiments that with the continuous optimization of the molar ratio of the above raw materials, the electrochemical performance of the final assembled battery continued to improve.
[0026] An appropriate amount of alumina promotes the phase change transformation of the base carbon material under high temperature conditions to form an appropriate amount of glassy carbon to improve the conductivity and mechanical strength of the base; an appropriate amount of alumina will also fully volatilize during the high-temperature calcination process and will not affect the conductivity of the assembled battery; if the amount is too large, the battery resistivity may increase due to residue, thereby affecting its rate performance.
[0027] (5) The heating polymerization is performed at a temperature of 60 to 120° C. for a time of 4 to 10 hours;
[0028] Optionally, the temperature of the heating polymerization is 80-100°C.
[0029] (6) The high temperature calcination is carried out at a temperature of 2100 to 2400° C. for a time of 2 to 5 hours;
[0030] Optionally, the high temperature calcination temperature is 2200-2400°C.
[0031] Further comparative tests revealed that if the high-temperature calcination temperature is low, such as 1500°C, no phase change occurs, the strength of the prepared porous carbon is low, and at this temperature, the residual alumina causes an increase in resistivity.
[0032] In an optional embodiment, in step (S1), the raw material further includes a nitrogen source;
[0033] The nitrogen source includes but is not limited to one or more of urea, melamine, and dicyandiamide;
[0034] Experiments have shown that the addition of a nitrogen source can further improve the electrical conductivity of porous carbon materials and enhance the rate performance of assembled batteries.
[0035] Optionally, the molar ratio of the nitrogen source to the aldehyde monomer is (0.01-0.5):2;
[0036] Further optionally, the molar ratio of the nitrogen source to the aldehyde monomer is (0.01-0.25):2.
[0037] In an optional embodiment, in step (S2), the physical activation comprises at least one of the following features (a) to (d):
[0038] (a) The physical activation, the activating agent is selected from one or more of CO, CO2, water vapor and oxygen;
[0039] Optionally, the activating agent is selected from one or more of CO, CO2, and water vapor.
[0040] (b) the physical activation is performed at a temperature of 700 to 1000° C.;
[0041] (c) the physical activation time is 2 to 15 hours;
[0042] (d) In the physical activation, the flow rate of the activator is 0.1 to 5 kg / h.
[0043] In an optional embodiment, in step (S3), the silicon deposition comprises at least one of the following features (1) to (4):
[0044] (1) The raw material gas used in the silicon deposition includes a silicon source gas;
[0045] Optionally, the silicon source gas is selected from conventional types in the art, including one or more of monosilane, disilane, dichlorosilane, and trichlorosilane.
[0046] (2) The flow rate of the raw gas is 1 to 15 L / min;
[0047] (3) The silicon deposition temperature is 400-580° C.;
[0048] (4) The silicon deposition time is 2 to 20 hours.
[0049] In an optional embodiment, in step (S3), the carbon coating comprises at least one of the following features (1) to (6):
[0050] (1) The raw material gas used in the carbon coating includes a carbon-containing gas;
[0051] (2) The carbon-containing gas is selected from one or more of C1-C4 alkanes, C2-C4 alkenes, and C2-C4 alkynes;
[0052] Optionally, the C1-C4 alkane is selected from methane, ethane, propane, and butane; optionally, the C2-C4 olefin is selected from ethylene, propylene, butene, and 1,3-butadiene; optionally, the C2-C4 alkyne is selected from acetylene, propyne, and butyne.
[0053] (3) The flow rate of the carbon-coated raw gas is 1 to 15 L / min;
[0054] (4) The carbon coating is performed at a temperature of 500 to 680° C.;
[0055] (5) The carbon coating time is 15 to 100 hours;
[0056] (6) The carbon coating is carried out under an inert atmosphere;
[0057] Optionally, the inert atmosphere is selected from an atmosphere containing an inert gas such as argon or helium.
[0058] In a second aspect, the present invention also provides a low expansion silicon-carbon negative electrode material prepared according to the above method.
[0059] In a third aspect, the present invention further provides a negative electrode plate, comprising the above-mentioned low expansion silicon-carbon negative electrode material.
[0060] In a fourth aspect, the present invention further provides a secondary battery, comprising the above-mentioned negative electrode plate.
[0061] Compared with the prior art, the present invention has the following beneficial results:
[0062] The invention discloses a method for preparing a low-expansion silicon-carbon negative electrode material, which uses aldehyde monomers and phenol monomers as raw materials, and additionally adds cyclohexamethyltetramine and aluminum oxide, and obtains a thermosetting phenolic resin through in-situ preparation. Cyclohexamethyltetramine is not only used as a polymerization catalyst and curing agent, but more importantly, it can optimize the pore structure of the porous carbon prepared subsequently, so that it has a suitable microporosity and pore volume, and forms a three-dimensional network structure, thereby enhancing its formation and stability; the introduction of aluminum oxide can promote the phase change of the carbon material during the subsequent high-temperature calcination process, from amorphous carbon to glassy carbon, further enhancing the hardness of the material and having high conductivity, and improving the integrity and stability of the porous carbon.
[0063] The porous carbon prepared by the specific method of the present invention has high strength, high conductivity and excellent pore structure. The battery assembled with the silicon-carbon negative electrode material prepared by using the porous carbon as the base has both high cycle stability and low expansion rate. DETAILED DESCRIPTION
[0064] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0065] In the description of the present invention, it should be noted that, for those of ordinary skill in the art, the specific meanings of the above terms in the present invention can be understood in specific circumstances. Below, according to the overall structure of the present invention, its embodiments are described. Unless otherwise specified, the raw materials in the embodiments of the present invention are purchased through commercial channels.
[0066] In a first aspect, the present invention provides a method for preparing a low expansion silicon-carbon negative electrode material, comprising:
[0067] (S1) uniformly mixing an aldehyde monomer, a phenol monomer, cyclohexamethylenetetramine and alumina, heating and polymerizing to obtain a thermosetting phenolic resin, and then calcining at a high temperature to obtain a high-strength carbon;
[0068] (S2) physically activating the high-strength carbon to obtain high-strength porous carbon;
[0069] (S3) Using the high-strength porous carbon as a substrate, sequentially performing silicon deposition and carbon coating to prepare the low-expansion silicon-carbon negative electrode material.
[0070] The present invention uses aldehyde monomers and phenol monomers as raw materials, and additionally adds cyclohexamethyltetramine and aluminum oxide, and obtains thermosetting phenolic resin by in-situ preparation. It is found through experiments that the addition of cyclohexamethyltetramine can be used as a polymerization catalyst and a curing agent. More importantly, it can optimize the pore structure of the porous carbon prepared subsequently, so that it has a suitable microporosity and pore volume, and forms a three-dimensional network structure, thereby enhancing its formation and stability; the introduction of aluminum oxide can promote the phase change of carbon materials during the subsequent high-temperature calcination process, from amorphous carbon to glassy carbon, further enhancing the hardness of the material and having high conductivity, and improving the integrity and stability of the porous carbon.
[0071] Further comparative tests found that if hexamethyltetramine was not added, the pore-forming effect was poor, the effective micropores were few, and there was a large amount of floating silicon on the porous carbon surface, resulting in poor cycle stability of the assembled battery, low capacity, and high electrode expansion rate.
[0072] Further comparative tests found that if alumina is not added, the phase transition from amorphous carbon to glassy carbon will not occur. High temperature will cause part of the pore structure to collapse, the original pore volume will be reduced, and the specific surface area will be reduced, which is not conducive to the subsequent deposition of nano-silicon particles. In addition, due to the change in the pore structure, the strength of the porous carbon is low, resulting in poor cycle stability of the assembled battery and a high electrode expansion rate.
[0073] Further comparative experiments found that if cyclohexamethylenetetramine is replaced with other common catalysts and / or curing agents prepared in phenolic resin, such as sodium hydroxide, the prepared porous carbon will have more macropores, which not only has poor integrity and stability, but also the nano-silicon particles are easily agglomerated in the macropores, increasing the resistivity and resulting in poor electrochemical performance of the assembled battery.
[0074] In an optional embodiment, step (S1) includes at least one of the following features (1) to (6):
[0075] (1) The aldehyde monomer is selected from formaldehyde;
[0076] Optionally, an aqueous formaldehyde solution is used;
[0077] Further optionally, the concentration of the formaldehyde aqueous solution is 35-40wt%, specifically 35wt%, 36wt%, 37wt%, 38wt%, 39wt%, 40wt% or any value within the above range.
[0078] (2) The phenolic monomer is selected from one or more of phenol, hydroquinone, and phloroglucinol;
[0079] (3) The molar ratio of the aldehyde monomer to the phenol monomer is 2:(0.01-2); specifically, it can be 2:0.01, 2:0.05, 2:0.1, 2:0.2, 2:0.5, 2:1, 2:1.2, 2:1.5, 2:2 or any ratio within the above range; optionally, the molar ratio of the aldehyde monomer to the phenol monomer is 2:(0.1-1).
[0080] (4) The molar ratio of cyclohexamethyltetramine, aluminum oxide and aldehyde monomer is (0.001-0.2): (0.001-0.05): 2;
[0081] Specifically, the molar ratio of cyclohexamethyltetramine to the aldehyde monomer can be 0.001:2, 0.002:2, 0.005:2, 0.01:2, 0.015:2, 0.020:2, 0.025:2, 0.030:2, 0.035:2, 0.040:2, 0.045:2, 0.050:2, 0.055:2, 0.060:2, 0.065:2, 0.070:2, 0.075:2, 0.080:2, 0.08 5:2, 0.090:2, 0.095:2, 0.1:2, 0.15:2, 0.2:2 or any ratio within the above range; the molar ratio of aluminum oxide to aldehyde monomer is 0.001:2, 0.002:2, 0.005:2, 0.01:2, 0.015:2, 0.020:2, 0.025:2, 0.030:2, 0.035:2, 0.040:2, 0.045:2, 0.050:2 or any ratio within the above range;
[0082] Optionally, the molar ratio of cyclohexamethyltetramine, aluminum oxide and aldehyde monomer is (0.005-0.15):(0.005-0.04):2.
[0083] Further optionally, the molar ratio of cyclohexamethyltetramine, aluminum oxide and aldehyde monomer is (0.01-0.1):(0.01-0.04):2.
[0084] It was found through experiments that with the continuous optimization of the molar ratio of the above raw materials, the electrochemical performance of the final assembled battery continued to improve.
[0085] An appropriate amount of alumina promotes the phase change transformation of the base carbon material under high temperature conditions to form an appropriate amount of glassy carbon to improve the conductivity and mechanical strength of the base; an appropriate amount of alumina will also fully volatilize during the high-temperature calcination process and will not affect the conductivity of the assembled battery; if the amount is too large, the battery resistivity may increase due to residue, thereby affecting its rate performance.
[0086] (5) The heating polymerization has a temperature of 60 to 120°C, specifically 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C, 95°C, 100°C, 105°C, 110°C, 105°C, 120°C or any value within the above range; optionally, the heating polymerization has a temperature of 80 to 100°C.
[0087] The heating polymerization time is 4 to 10 hours; specifically, it can be 4.0 hours, 4.5 hours, 5.0 hours, 5.5 hours, 6.0 hours, 6.5 hours, 7.0 hours, 7.5 hours, 8.0 hours, 8.5 hours, 9.0 hours, 9.5 hours, 10 hours or any value within the above range.
[0088] (6) The high temperature calcination is performed at a temperature of 2100-2400°C, specifically 2100°C, 2150°C, 2200°C, 2250°C, 2300°C, 2350°C, 2400°C or any value within the above range; optionally, the high temperature calcination temperature is 2200-2400°C.
[0089] The high temperature calcination time is 2 to 5 hours; specifically, it can be 2.0 hours, 2.5 hours, 3.0 hours, 3.5 hours, 4.0 hours, 4.5 hours, 5.0 hours or any value within the above range.
[0090] Further comparative tests revealed that if the high-temperature calcination temperature is low, such as 1500°C, no phase change occurs, the strength of the prepared porous carbon is low, and at this temperature, the residual alumina causes an increase in resistivity.
[0091] In an optional embodiment, in step (S1), the raw material further includes a nitrogen source;
[0092] The nitrogen source includes but is not limited to one or more of urea, melamine, and dicyandiamide;
[0093] Experiments have shown that the addition of a nitrogen source can further improve the electrical conductivity of porous carbon materials and enhance the rate performance of assembled batteries.
[0094] Optionally, the molar ratio of the nitrogen source to the aldehyde monomer is (0.01-0.5):2; specifically, it can be 0.01:2, 0.02:2, 0.05:2, 0.1:2, 0.15:2, 0.2:2, 0.25:2, 0.3:2, 0.35:2, 0.4:2, 0.45:2, 0.5:2 or any ratio within the above range; further optionally, the molar ratio of the nitrogen source to the aldehyde monomer is (0.01-0.25):2.
[0095] In an optional embodiment, in step (S2), the physical activation comprises at least one of the following features (a) to (d):
[0096] (a) The physical activation, the activating agent is selected from one or more of CO, CO2, water vapor and oxygen;
[0097] Optionally, the activating agent is selected from one or more of CO, CO2, and water vapor.
[0098] (b) The physical activation is carried out at a temperature of 700-1000°C; specifically, it can be 700°C, 720°C, 740°C, 760°C, 780°C, 800°C, 820°C, 840°C, 860°C, 880°C, 900°C, 950°C, 1000°C or any value within the above range; optionally, the temperature is 800-900°C.
[0099] (c) The physical activation time is 2 to 15 h, specifically 2 h, 2.5 h, 3.0 h, 3.5 h, 4.0 h, 4.5 h, 5.0 h, 6 h, 7 h, 8 h, 9 h, 10 h, 11 h, 12 h, 13 h, 14 h, 15 h or any value within the above range.
[0100] (d) The physical activation has a flow rate of the activator of 0.1 to 5 kg / h, specifically 0.1 kg / h, 0.5 kg / h, 1 kg / h, 1.5 kg / h, 2 kg / h, 2.5 kg / h, 3 kg / h, 3.5 kg / h, 4 kg / h, 4.5 kg / h, 5 kg / h or any value within the above range.
[0101] In an optional embodiment, in step (S3), the silicon deposition comprises at least one of the following features (1) to (4):
[0102] (1) The raw material gas used in the silicon deposition includes a silicon source gas;
[0103] Optionally, the silicon source gas is selected from conventional types in the art, including one or more of monosilane, disilane, dichlorosilane, and trichlorosilane.
[0104] (2) The flow rate of the raw gas is 1 to 15 L / min; specifically, it can be 1 L / min, 2 L / min, 3 L / min, 5 L / min, 8 L / min, 10 L / min, 12 L / min, 15 L / h or any value within the above range.
[0105] (3) The silicon deposition temperature is 400-580°C, specifically 400°C, 420°C, 450°C, 480°C, 500°C, 520°C, 550°C, 580°C or any value within the above range.
[0106] (4) The silicon deposition time is 2 to 20 hours, specifically 2 hours, 5 hours, 8 hours, 10 hours, 12 hours, 15 hours, 18 hours, 20 hours or any value within the above range.
[0107] In an optional embodiment, in step (S3), the carbon coating comprises at least one of the following features (1) to (6):
[0108] (1) The carbon coating adopts a raw material gas including a carbon-containing gas;
[0109] (2) the carbon-containing gas is selected from one or more of C1-C4 alkanes, C2-C4 alkenes, and C2-C4 alkynes;
[0110] Optionally, the C1-C4 alkane is selected from methane, ethane, propane, and butane; optionally, the C2-C4 olefin is selected from ethylene, propylene, butene, and 1,3-butadiene; optionally, the C2-C4 alkyne is selected from acetylene, propyne, and butyne.
[0111] (3) The flow rate of the carbon-coated raw gas is 1 to 15 L / min; specifically, it can be 1 L / min, 2 L / min, 3 L / min, 5 L / min, 8 L / min, 10 L / min, 12 L / min, 15 L / h or any value within the above range.
[0112] (4) The carbon coating has a temperature of 500-680°C, specifically 500°C, 520°C, 550°C, 580°C, 600°C, 620°C, 650°C, 680°C or any value within the above range.
[0113] (5) The carbon coating time is 15 to 100 hours, specifically 15 hours, 20 hours, 25 hours, 30 hours, 35 hours, 40 hours, 45 hours, 50 hours, 55 hours, 60 hours, 65 hours, 70 hours, 75 hours, 80 hours, 85 hours, 90 hours, 95 hours, 100 hours or any value within the above range.
[0114] (6) The carbon coating is carried out under an inert atmosphere;
[0115] Optionally, the inert atmosphere is selected from an atmosphere containing an inert gas such as argon or helium.
[0116] In a second aspect, the present invention also provides a low expansion silicon-carbon negative electrode material prepared according to the above method.
[0117] In a third aspect, the present invention further provides a negative electrode plate, comprising the above-mentioned low expansion silicon-carbon negative electrode material.
[0118] In a fourth aspect, the present invention further provides a secondary battery, comprising the above-mentioned negative electrode plate.
[0119] Example 1
[0120] (S1) 42.2 kg of formaldehyde aqueous solution (37 wt%, 520 mol based on formaldehyde in the solution) and 9.8 kg of phenol (104 mol) are added to a reactor, followed by the addition of 1.64 kg of melamine (13 mol), 0.7 kg of cyclohexamethyltetramine (5 mol) and 0.66 kg of Al2O3 (6.5 mol). After stirring evenly, the mixture is heated at 100°C for 6 h, and the resulting thermosetting phenolic resin is calcined at 2200°C for 3 h to obtain high-strength carbon.
[0121] (S2) placing the above 10 kg high-strength carbon in a rotary kiln, evacuating the kiln, backfilling with inert gas, maintaining an inert atmosphere in the kiln, controlling the oxygen content in the kiln below 1000 ppm, adjusting the rotary kiln speed to 5 r / min, raising the temperature to 800 °C at 5 °C / min to activate the high-strength carbon, using water vapor as the activation process gas, with an inlet flow rate of 2 kg / h, and a physical activation time of 10 h; obtaining a specific surface area of 1850 m 2 / g, pore volume is 0.91cm 3 / g of high-strength porous carbon particles, the activated high-strength porous carbon particles are coarsely crushed and graded to obtain D 50 =7.5μm high-strength porous carbon.
[0122] (S3) 10 kg of high-strength porous carbon was added to a rotary kiln as a substrate. Under a nitrogen atmosphere, monosilane gas was introduced into the deposition furnace at a flow rate of 5 L / min. The temperature of the deposition furnace was maintained at 450° C. The gas was continuously ventilated until a silicon deposition layer was continuously nucleated inside and on the surface of the porous carbon material. The venting time was maintained for 10 hours to obtain a silicon / carbon material.
[0123] (S4) The above silicon / carbon material is added into a CVD furnace, acetylene gas is introduced at a flow rate of 1 L / min under a nitrogen atmosphere, and carbon coating is carried out by deposition at 590° C. for 23 hours. The carbon coating amount is 4 wt% (based on the product). After being broken up, screened, and demagnetized, a low expansion silicon-carbon composite negative electrode material is obtained.
[0124] Example 2
[0125] The preparation process is substantially the same as that of Example 1, except that in step (S1), melamine is replaced by an equal molar amount of urea.
[0126] Example 3
[0127] The preparation process is basically the same as that of Example 1, except that in step (S1), the calcination temperature is replaced with 2400° C. and the time is 3 h.
[0128] Example 4
[0129] The preparation process is basically the same as that of Example 1, except that in step (S1), the mass of Al2O3 is replaced by 1.04 kg (10.2 mol).
[0130] Example 5
[0131] The preparation process is basically the same as that of Example 1, except that in step (S1), the mass of Al2O3 is replaced by 0.14 kg (1.4 mol).
[0132] Example 6
[0133] The preparation process is substantially the same as that of Example 1, except that in step (S1), the mass of cyclohexamethyltetramine is replaced with 5.47 kg (39 mol).
[0134] Example 7
[0135] The preparation process is substantially the same as that of Example 1, except that in step (S1), the mass of cyclohexamethyltetramine is replaced with 0.18 kg (1.3 mol).
[0136] Example 8
[0137] The preparation process is substantially the same as that of Example 1, except that melamine is not added in step (S1).
[0138] Comparative Example 1
[0139] The preparation process is substantially the same as that of Example 1, except that cyclohexamethyltetramine is not added in step (S1).
[0140] Comparative Example 2
[0141] The preparation process is basically the same as that of Example 1, except that no alumina is added in step (S1).
[0142] Comparative Example 3
[0143] The preparation process is substantially the same as that of Example 1, except that in step (S1), cyclohexamethyltetramine is replaced by an equimolar amount of sodium hydroxide.
[0144] Comparative Example 4
[0145] The preparation process is substantially the same as that of Example 1, except that in step (S1), the mass of aluminum oxide is replaced with 1.59 kg (15.6 mol).
[0146] Comparative Example 5
[0147] The preparation process is substantially the same as that of Example 1, except that in step (S1), the mass of cyclohexamethyltetramine is replaced with 8.02 kg (57.2 mol).
[0148] Comparative Example 6
[0149] The preparation process is basically the same as that of Example 1, except that in step (S1), the calcination temperature is replaced with 1500° C. and the time is 3 h.
[0150] The performance data of the porous carbon prepared in each embodiment and comparative example are listed in the following Table 1, wherein the microporosity, mesoporosity, macroporosity and pore volume are tested by Micromeritics 3020.
[0151] Table 1
[0152]
[0153]
[0154] The performance test data of the low expansion silicon-carbon composite negative electrode materials prepared in each embodiment and comparative example are listed in the following Table 2, wherein the particle size test is performed by Malvern 3000 test, the powder resistance is measured by a semiconductor powder resistivity tester (30MPa four-probe V1.4), the tap density is measured by a tap density meter, and the specific surface area is tested by a Micrometer 3020.
[0155] Table 2
[0156]
[0157]
[0158] Application Examples
[0159] Batteries were assembled using the products prepared in each embodiment and each comparative example as negative electrode materials.
[0160] (1) Preparation of positive electrode sheets: The positive electrode active material lithium nickel cobalt manganese oxide (NCM811), the conductive agent SuperP, carbon nanotubes, the binder polyvinylidene fluoride (PVDF) and N-methylpyrrolidone (NMP) were mixed in a mass ratio of 97:1:0.5:1.5 to form a positive electrode slurry (solid content of 70 wt%), which was coated on both sides of the current collector aluminum foil, dried at 100°C, and cold pressed at 4 MPa at room temperature, and then trimmed, cut, and slit, and the tabs were welded to form positive electrode sheets.
[0161] (2) Preparation of negative electrode sheets: Under a nitrogen protective atmosphere, the solvent N-methylpyrrolidone (NMP) and the binder PVDF were stirred and mixed, and then the conductive agent SuperP was added and stirred and mixed. Then, the products prepared in each embodiment and each comparative example were added as negative electrode active materials and stirred and mixed thoroughly to prepare a negative electrode slurry (solid content of 50wt%).
[0162] The negative electrode slurry is coated on both sides of the current collector copper foil, dried at 100°C, cold pressed at 4MPa at room temperature, and then trimmed, cut, stripped, and the tabs are welded to make negative electrode sheets.
[0163] (3) Assembly of lithium-ion batteries
[0164] Using PE porous polymer film as separator, the prepared positive electrode sheet, separator and negative electrode sheet are stacked in order, with the separator placed between the positive and negative electrode sheets, and wound to obtain a bare battery cell; the bare battery cell is placed in an aluminum-plastic shell package and placed under a relative vacuum pressure of -0.95×10 5 Pa, dried at 100 ° C to a moisture content of less than 100 ppm. The electrolyte is injected into the dried bare battery, wherein the electrolyte consists of ethylene carbonate (EC), ethyl methyl carbonate (EMC) and diethyl carbonate (DEC) (EC:EMC:DEC volume ratio = 1:1:1) and LiPF6 (1.0M), and is packaged, left to stand, formed (0.02C constant current charging for 2h, 0.1C constant current charging for 2h), shaped, and capacity tested (capacity division) to make a soft-pack liquid lithium-ion battery.
[0165] When assembling the battery, five batteries are prepared for each test, and a total of five sets of data are tested. The final performance is the average value of the five sets of data.
[0166] The battery cycle performance is tested on the Xinwei equipment, specifically:
[0167] At 25°C, first discharge at 0.1C to 0.005V, then discharge at 0.08C to 0.001V, discharge at 0.05C to 0.001V, discharge at 0.02C to 0.001V, and let stand for 10 minutes; then charge to 1.5V at 0.1C, let stand for 10 minutes, record the charge and discharge capacity after the first cycle, and calculate the first coulomb efficiency; cycle 100 times in the above manner, record the charge and discharge capacity after 100 times, and calculate the capacity retention rate after 100 cycles. The test and calculation process of the capacity retention rate after 500 cycles adopt the same method. The specific test / calculation results are shown in Table 3 below.
[0168] Table 3
[0169]
[0170]
[0171] Comparing Examples 1 to 8 in Table 3, the silicon-carbon negative electrode materials prepared in each example have excellent cycle stability and low expansion rate. The electrochemical performance of the product prepared in Example 1 is the best, and the cycle stability of the product prepared in Example 7 is slightly worse and the expansion rate is slightly higher. This may be because the amount of cyclohexamethyltetramine added is slightly lower, the effective micropores in the porous carbon are slightly less, there is a small amount of floating silicon on the surface, and the expansion rate is reduced.
[0172] Comparing Example 1 with Comparative Example 1, the product prepared in Comparative Example 1 has low capacity, poor cycle and high expansion rate, which may be because no cyclohexamethyltetramine is added, the pore-forming effect is poor, there are very few effective micropores in the porous carbon, and there is a large amount of floating silicon on the surface, and the resistivity is high.
[0173] Comparing Example 1 and Comparative Example 2, the product prepared in Comparative Example 2 has low capacity, poor cycle and high expansion rate, which may be because no alumina is added, and the prepared porous carbon substrate has low pore volume, low degree of polymerization, low hardness and poor stability.
[0174] Comparing Example 1 and Comparative Example 3, the product prepared in Comparative Example 3 has poor circulation and high expansion rate, which may be because cyclohexamethyltetramine is replaced with sodium hydroxide, resulting in a small proportion of micropores in the prepared porous carbon substrate, an increased macroporosity, a low deposition amount and the occurrence of nano-silicon agglomeration.
[0175] Comparing Example 1 with Comparative Example 4, the excess aluminum oxide in Comparative Example 4 is not completely volatilized and occupies part of the pore structure, affecting the deposition effect of silicon, and excessive dosage will cause the substrate resistance to increase instead of decrease, thereby affecting its rate performance.
[0176] Comparing Example 1 with Comparative Example 5, the product prepared in Comparative Example 5 has low capacity, poor circulation, and high expansion rate. This may be because the amount of cyclohexamethyltetramine added is too large, resulting in micropores connecting into macropores, resulting in a decrease in pore volume and the occurrence of nano-silicon agglomeration.
[0177] Comparing Example 1 with Comparative Example 6, the product prepared in Comparative Example 6 has low capacity, poor circulation, and high expansion rate. This may be because the temperature of high-temperature calcination is too low. On the one hand, the alumina is not completely released and still occupies a certain pore volume, resulting in a decrease in the pore volume of the porous carbon substrate; on the other hand, it affects the phase change conversion, and the prepared porous carbon substrate has poor strength and stability.
[0178] The above-mentioned embodiments are preferred embodiments, but the protection scope of the present invention is not limited thereto. A person skilled in the art can easily understand the spirit of the present invention based on the above-mentioned embodiments and make different extensions and changes. However, as long as they do not deviate from the spirit of the present invention, they are all within the protection scope of the present invention.
Claims
1. A method for preparing a low expansion silicon-carbon negative electrode material, characterized in that: include: (S1) uniformly mixing an aldehyde monomer, a phenol monomer, cyclohexamethylenetetramine and alumina, heating and polymerizing to obtain a thermosetting phenolic resin, and then calcining at a high temperature to obtain a high-strength carbon; (S2) physically activating the high-strength carbon to obtain high-strength porous carbon; (S3) Using the high-strength porous carbon as a substrate, sequentially performing silicon deposition and carbon coating to prepare the low-expansion silicon-carbon negative electrode material.
2. The method for preparing the low expansion silicon-carbon negative electrode material according to claim 1, characterized in that: In step (S1), at least one of the following features (1) to (6) is included: (1) The aldehyde monomer is selected from formaldehyde; (2) The phenolic monomer is selected from one or more of phenol, hydroquinone, and phloroglucinol; (3) The molar ratio of aldehyde monomer to phenol monomer is 2:(0.01-2); (4) The molar ratio of cyclohexamethyltetramine, aluminum oxide and aldehyde monomer is (0.001-0.2): (0.001-0.05): 2; (5) the heating polymerization is performed at a temperature of 60 to 120° C. for a time of 4 to 10 hours; (6) The high temperature calcination is carried out at a temperature of 2100 to 2400° C. and for a time of 2 to 5 hours.
3. The method for preparing the low expansion silicon-carbon negative electrode material according to claim 2, characterized in that: In step (S1), the molar ratio of cyclohexamethyltetramine, aluminum oxide and aldehyde monomer is (0.005-0.15): (0.005-0.04):
2.
4. The method for preparing a low expansion silicon-carbon negative electrode material according to claim 1, characterized in that: In step (S1), the raw material also includes a nitrogen source; The nitrogen source includes but is not limited to one or more of urea, melamine, and dicyandiamide; The molar ratio of the nitrogen source to the aldehyde monomer is (0.01-0.5):
2.
5. The method for preparing a low expansion silicon-carbon negative electrode material according to claim 1, characterized in that: In step (S2), the physical activation comprises at least one of the following features (a) to (d): (a) The physical activation, the activating agent is selected from one or more of CO, CO2, water vapor and oxygen; (b) the physical activation is performed at a temperature of 700 to 1000° C.; (c) the physical activation time is 2 to 15 hours; (d) In the physical activation, the flow rate of the activator is 0.1 to 5 kg / h.
6. The method for preparing a low expansion silicon-carbon negative electrode material according to claim 1, characterized in that: In step (S3), the silicon deposition comprises at least one of the following features (1) to (4): (1) The raw material gas used in the silicon deposition includes a silicon source gas; (2) The flow rate of the raw gas is 1 to 15 L / min; (3) The silicon deposition temperature is 400-580° C.; (4) The silicon deposition time is 2 to 20 hours.
7. The method for preparing a low expansion silicon-carbon negative electrode material according to claim 1, characterized in that: In step (S3), the carbon coating comprises at least one of the following features (1) to (6): (1) The raw material gas used in the carbon coating includes a carbon-containing gas; (2) the carbon-containing gas is selected from one or more of C1-C4 alkanes, C2-C4 alkenes, and C2-C4 alkynes; (3) The flow rate of the carbon-coated raw gas is 1 to 15 L / min; (4) The carbon coating is performed at a temperature of 500 to 680° C.; (5) The carbon coating time is 15 to 100 hours; (6) The carbon coating is carried out under an inert atmosphere.
8. A low expansion silicon-carbon negative electrode material prepared by the method according to any one of claims 1 to 7.
9. A negative electrode plate, characterized in that: Comprising the low expansion silicon-carbon negative electrode material as described in claim 8.
10. A secondary battery, characterized in that: Comprising the negative electrode sheet as claimed in claim 9.
Citation Information
Cited By
Pre-lithiated silicon-carbon negative electrode, negative electrode plate, secondary battery and preparation method of pre-lithiated silicon-carbon negative electrode
CN120497302A